The impact of foreign shareholdings and originating countries on banking sector efficiency - Chan, S.G.; Koh, E.H.Y. (2015)

(untitled)
This study analyses the effects of foreign shareholdings on the ASEAN-5 banking sector performance using the Stochastic Frontier Analysis based Battese and Coelli (1995) model. Unlike most extant studies which compared the performance of local and foreign banks, this study assessed how foreign shareholdings of banks in a given country affect its banking sector's performance. It also evaluates the resource-based approach to differentiate the impact of the different origins of the foreign shareholdings. This paper's findings also present public policy implications because foreign shareholdings especially those from the more developed countries contribute positively to bank performance. This study presents three findings. First, foreign shareholding concentration affects bank efficiencies positively. Second, the foreign shareholders' countries of origin matter, but Asian countries had the greatest impact, perhaps a reflection of proximity and familiarity. In sum, foreign shareholdings have contributed positively to bank efficiency by reducing agency costs and enhancing the bank's resource base. Third, excessive regulation worsens banks' profit efficiency.